Description of Hand Hygiene’s Compliance on Nurse of Hemodialysis at Haji Hospital Surabaya - Rr Rizqi Saphira Nurani; Atik Choirul Hidajah (Universitas Airlangga, 2017)
Thousands of patients around the world die every day due to infection when getting health care. This is due to the transmission of pathogenic micro bacteria from the hands of health workers during receiving health care. Hand hygiene is the most important aspect to prevent the transmission of pathogenic micro bacteria and prevent Hospital Acquired Infections (HAIs). Awareness of hand hygiene in health workers is a fundamental behavior in efforts to prevent cross-infection. The purpose of this study was to conduct an evaluation of compliance with hand hygiene at the Hemodialysis Unit nurses at the Haji Public Hospital, Surabaya. This type of research is a descriptive study and observation using a qualitative approach. Data collection techniques in this study were interviews with nurses of the Hemodialysis Unit, and hand hygiene audits. The research instrument used a hand hygiene knowledge questionnaire, Blood Stream Infection (BSI) knowledge questionnaire, and a hand hygiene audit form prepared by WHO. The population in this study were all nurses in the Hemodialysis Unit of the Haji Public Hospital, Surabaya, amounting to 11 people. The results of this study found that the compliance of the hand hygiene nurses of the Hemodialysis Unit was 35%. The compliance rate is still lacking and does not meet the standards set by the Infection Control and Prevention Program (IPC) of the Haji Public Hospital, Surabaya which is 100% and still does not meet the WHO compliance standard of 40%. The low hand hygiene compliance rate is caused by the low participation of basic PPI training and the lack of availability of hand hygiene facilities in the Hemodialysis Unit of the Haji Public Hospital, Surabaya. Suggestions from this research are to do on the job training on how to do proper hand hygiene and improve hand hygiene facilities in the Hemodialysis Unit.